2021
DOI: 10.21037/jtd-21-137
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of visceral pleural invasion using confocal laser endomicroscopy during lung cancer surgery

Abstract: Background: Visceral pleural invasion (VPI) in lung cancer is a significant prognostic factor; however, it is difficult to diagnose preoperatively or intraoperatively. In this study, we examined the possibility of intraoperative diagnosis of VPI using confocal laser endomicroscopy (CLE). Methods: Among patients with primary lung cancer who underwent surgery between April 2018 and August 2019, those in whom the tumor was in contact with the pleura on chest computed tomography and whose pleural changes were intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Xie et al ( 14 ) reported that the accuracy, sensitivity, and specificity of intraoperative autofluorescence staining of frozen sections in the diagnosis of VPI of lung adenocarcinoma ≤2 cm were 95.5%, 86.8%, and 100%, respectively. Sawada et al ( 18 ) calculated that the diagnosis accuracy of confocal laser endomicroscopy was as high as 86.7%. These findings are conducive to the decision-making of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al ( 14 ) reported that the accuracy, sensitivity, and specificity of intraoperative autofluorescence staining of frozen sections in the diagnosis of VPI of lung adenocarcinoma ≤2 cm were 95.5%, 86.8%, and 100%, respectively. Sawada et al ( 18 ) calculated that the diagnosis accuracy of confocal laser endomicroscopy was as high as 86.7%. These findings are conducive to the decision-making of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…VPI is graded as PL1 and PL2, and it is recommended that EFs staining should be evaluated when hematoxylin-eosin (HE) staining does not clearly distinguish PL0 from PL1 ( 6 ). Several studies have regarded the significance of accurate prediction and diagnosis of VPI for treatment decisions of lung cancer patients in the preoperative and intraoperative stages ( 7 - 18 ). Therefore, this review summarizes the recent research in predicting VPI.…”
Section: Introductionmentioning
confidence: 99%
“…In malignant pleural effusion, a pilot study demonstrated that pCLE was capable of detecting malignant cells of pleural effusion rapidly and simply [46]. Moreover, SAWADA et al [47] investigated the feasibility of intraoperative detection of visceral pleural invasion (VPI) using pCLE imaging in patients with primary lung cancer. They demonstrated that the accuracy rate in the diagnosis of VPI through pCLE was 86.7%.…”
Section: Pleuramentioning
confidence: 99%
“…Moreover, S awada et al . [ 47 ] investigated the feasibility of intraoperative detection of visceral pleural invasion (VPI) using pCLE imaging in patients with primary lung cancer. They demonstrated that the accuracy rate in the diagnosis of VPI through pCLE was 86.7%.…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation